MAXIMIZATION OF PRE-HARVEST, HARVEST AND POST-HARVEST HANDLING AS AN EFFORT TO MAINTAIN WOTEL QUALITY - Wahyudi; Pangaribuan, Darwin H. (Universitas Veteran Bangun Nusantara, 2025)
Carrots (Daucus carota) are quite popular vegetables because they have a lot of nutritional content that is very good for health. To produce good quality carrots, it is necessary to carry out good pre-harvest and post-harvest activities, so that the nutritional content of carrots can be maintained properly. However, it should be noted that many pre-harvest and post-harvest activities are not right, resulting in poor quality carrots. Therefore, the purpose of this review is to find out the right pre-harvest, harvest and post-harvest activities to maintain the quality of carrots. This review is sourced from various journals, books and relevant articles. Pre-harvest activities that need to be considered include providing the right nutrition, determining the time of harvest and good harvest handling activities. Proper post-harvest activities can produce long shelf life and maintain the nutritional content of carrots. Regular consumption of carrots can maintain body health because the nutritional content of carrots is good for the body. Keywords: fertilization, storage, shelf life, health, production